Detection of bacterial antigens and Alzheimer’s disease-like pathology in the central nervous system of BALB/c mice following intranasal infection with a laboratory isolate of Chlamydia pneumoniae - Little, Christopher S.; Joyce, Timothy A.; Hammond, Christine J.; Matta, Hazem; Cahn, David; Appelt, Denah M.; Balin, Brian J. (Frontiers in Aging Neuroscience, 2014)
Pathology consistent with that observed in Alzheimer’s disease (AD) has previously been documented following intranasal infection of normal wild-type mice with Chlamydia pneumoniae (Cpn) isolated from an AD brain (96-41). In the current study, BALB/c mice were intranasally infected with a laboratory strain of Cpn, AR-39, and brain and olfactory bulbs were obtained at 1-4 months post-infection (pi). Immunohistochemistry for amyloid beta or Cpn antigens was performed on sections from brains of infected or mock-infected mice. Chlamydia-specific immunolabeling was identified in olfactory bulb tissues and in cerebrum of AR-39 infected mice. The Cpn specific labeling was most prominent at 1 month pi and the greatest burden of amyloid deposition was noted at 2 months pi, whereas both decreased at 3 and 4 months. Viable Cpn was recovered from olfactory bulbs of 3 of 3 experimentally infected mice at 1 and 3 months pi, and in 2 of 3 mice at 4 months pi. In contrast, in cortical tissues of infected mice at 1 and 4 months pi no viable organism was obtained. At 3 months pi, only 1 of 3 mice had a measurable burden of viable Cpn from the cortical tissues. Mock-infected mice (0 of 3) had no detectable Cpn in either olfactory bulbs or cortical tissues. These data indicate that the AR-39 isolate of Cpn establishes a limited infection predominantly in the olfactory bulbs of BALB/c mice. Although infection with the laboratory strain of Cpn promotes deposition of amyloid beta, this appears to resolve following reduction of the Cpn antigen burden over time. Our data suggest that infection with the AR-39 laboratory isolate of Cpn results in a different course of amyloid beta deposition and ultimate resolution than that observed following infection with the human AD-brain Cpn isolate, 96-41. These data further support that there may be differences, possibly in virulence factors, between Cpn isolates in the generation of sustainable AD pathology.